The Effect of Feeding Indigofera zollingeriana on Milk Production and Quality of Jawa Randu Goats in Kalukku District, West Sulawesi - Silvi Silvi; AN. Insani; Mariam Mariam; N. Nurdin; NS. Rullah (Jurnal Ternak, 2026)
Jawa Randu goats are one of the local livestock breeds with considerable potential for milk production; however, both productivity and milk quality are highly influenced by feeding factors. This study aimed to evaluate the effect of Indigofera zollingeriana supplementation on milk production and quality of Jawa Randu goats in Kalukku District, West Sulawesi, Indonesia. The experiment was conducted from January to February 2026 using a Completely Randomized Design (CRD) with three treatments and five replications, involving a total of 15 goats. The treatments consisted of P1 (Pakchong Napier grass + 10% Indigofera zollingeriana), P2 (Pakchong Napier grass + 20% Indigofera zollingeriana), and P3 (Pakchong Napier grass + 30% Indigofera zollingeriana). The observed parameters included milk production and physical quality of milk (pH, specific gravity, and viscosity). Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s multiple range test. The results showed that supplementation with Indigofera zollingeriana had a significant effect (P < 0.05) on milk production of Jawa Randu goats, with the highest yield observed in treatment P2. However, the treatments did not significantly affect (P > 0.05) the physical quality of milk. The values of pH, specific gravity, and viscosity remained within normal ranges. In conclusion, the inclusion of Indigofera zollingeriana in the diet can improve milk production without adversely affecting the physical quality of milk.